To solve the equation \( \frac{2}{3}(x - 6) = 14 \), follow these steps:
-
Eliminate the fraction by multiplying both sides of the equation by 3:
\[ 3 \cdot \frac{2}{3}(x - 6) = 3 \cdot 14 \]
This simplifies to:
\[ 2(x - 6) = 42 \]
-
Distribute the 2 on the left side:
\[ 2x - 12 = 42 \]
-
Add 12 to both sides to isolate the term with \(x\):
\[ 2x - 12 + 12 = 42 + 12 \]
This simplifies to:
\[ 2x = 54 \]
-
Divide by 2 to solve for \(x\):
\[ x = \frac{54}{2} \]
This simplifies to:
\[ x = 27 \]
So, the solution is \( \boxed{27} \).